PENGARUH LATIHAN PLYOMETRIC FROG JUMP DAN SINGLE LEG SPEED HOP TERHADAP KEMAMPUAN SHOOTING SEPAKBOLA SISWA SMPN 21 MALANG JUDUL - Arif Wibowo; Eko Hariyanto; Agus Tomi (Fakultas Ilmu Keolahragaan UM)
ABSTRACT: The purpose of this study was to determine the difference between the effect of the combination of exercise plyometric frog jump and speed single leg hop with conventional exercise to increase the ability of shooting football. The design of the study is a purely experimental research (true experimental). The sampling technique sistimatic been using the technique of random sampling. The division of the group to the experimental group and the control group using ordinal pairing techniques matching. Collecting data using pure experiment and observation preliminary tests. Analysis of data using inferential statistics such as analysis of variance test of the track comes up in the form of the t test. The results of the analysis of single-lane (ANOVA) was obtained F count equal 0.0556 < F table 2.82 of the significance of 0.05. Results of t test replicates observations obtained t count of 66.3593 > t table 2,228 for the experimental group and the conventional practice of 38.3905 obtained t count > t table 2.228 at the 0.05 significance. Independent samples t test results obtained by 6.272198 t count>t table 2.262 at the 0.05 significance.Key words: Combination Plyometric, Frog Jump, Single Leg Speed Hop, Conventional Exercise, Shooting Football.